Incisional Morphine Has No Analgesic Effect on Postoperative Pain Following Inguinal Herniotomy. Issue 1 (January 1998) - Rosenstock, C.; Rasmussen, H.; Andersen, G.; Lund, C.
Abstract : Background and Objectives: Opioids induce antinociceptive effects after peripheral administration in experimental and clinical studies. The results of the clinical studies are conflicting. The objective of this study was to examine a possible analgesic effect of incisionally administered morphine on postoperative pain in patients undergoing inguinal herniotomy during general anesthesia. Methods: Forty-six consecutive outpatients were included in a double-blind, randomized, placebo-controlled study. At conclusion of herniotomy 5 mg morphine was injected incisionally in 11 patients, intravenously in 10, and subcutaneously in 13. The placebo group of 12 had saline injected in the incision. Postoperative pain at rest and during mobilization was assessed with a visual analog scale. Assessments were made immediately before and after herniotomy, at 2, 4, and 6 hours after surgery, and on the second and seventh postoperative day. Postoperative morphine and acetaminophen consumptions were recorded within the same period. Results: There were no significant differences in visual analog scores between the groups at any time during the study. Overall differences in postoperative acetaminophen and morphine consumptions were insignificant. Conclusions: The analgesic effect of a single 5 mg dose of morphine injected in a herniotomy wound is not superior to saline or to morphine given subcutaneously or intravenously.